Kim Bu: A Study of Joan Kim Erkan’s Novel Lady Who as a Watermark Translation and its Retro-translation into Turkish - Sinem Sancaktaroğlu Bozkurt; Yeşim Sönmez Dinçkan (İstanbul Üniversitesi Çeviribilim Dergisi)
The study focuses on the novel Lady Who by Joan Kim Erkan, a Welsh woman who narrates the last sixty years of Turkey by blending her personal experiences with the cities of Istanbul and Aydın in the background, and Kim Bu, its Turkish translation by Zeynep Avcı. Lady Who, which is produced as an original work in English, is analysed as a product produced as a result of a mental translation process, referring to the concept of “watermark translation” coined by Sündüz Öztürk Kasar, while its Turkish translation is examined referring to the concept of "retro-translation" under the headings of proper names, forms of address, idioms, phrases, historical features, religious features, cultural features related to food, social life, traditions and customs. How the author conveys these Turkish cultural features to the English reader and thus how the English work and its Turkish retro-translation are positioned as translations are examined with a descriptive approach. After briefly describing the author and the translator, the concepts of watermark translation and retro-translation are explained. The cultural features are then comparatively examined under subcategories, and the findings are presented. Finally, a general conclusion is presented by evaluating the data through representative examples.